Whole-Genome Sequencing of Corynebacterium diphtheriae Isolates Recovered from an Inner-City Population Demonstrates the Predominance of a Single Molecular Strain - Chorlton, Samuel D. (J Clin Microbiol, 2020)
In some parts of the world, Corynebacterium diphtheriae has reemerged as a pathogen, especially as a cause of infections among impoverished and marginalized populations. We performed whole-genome sequencing (WGS) on all cutaneous C. diphtheriae isolates (n = 56) from Vancouver’s inner-city population over a 3-year time period (2015 to 2018). All isolates with complete genome assembly were toxin negative, contained a common set of 22 virulence factors, and shared a highly conserved accessory genome. One of our isolates harbored a novel plasmid conferring macrolide and lincosamide resistance. Fifty-two out of 56 isolates were multilocus sequence type 76, and single nucleotide variants (SNV) and core-genome multilocus sequence typing (cgMLST) analysis demonstrated tight clustering of our isolates relative to all publicly available C. diphtheriae genomes. All sequence type 76 (ST76) study isolates were within a median of 22 SNVs and 13 cgMLST alleles of each other, while NCBI genomes were within a median of 17,436 SNVs and 1,552 cgMLST alleles of each other (both P < 2.2 × 10(−16)). A single strain of C. diphtheriae appears to be causing cutaneous infections in the low-income population of Vancouver. Further research is needed to elucidate transmission networks in our study population and standardize C. diphtheriae epidemiological typing when whole genomes are sequenced.